A arte vai à luta: resistência artística na Itália fascista - Teles, Beatriz Nascimento (2017)
This dissertation aims to analyze the Italian artistic antifascist resistance, shaped with the film Ossessione, directed by Luchino Visconti. The authors of the film met each other through the Cinema magazine, where all worked between the late 1930’s and early 1940’s, temporal cut that we choose in this work. This period of time was chosen for two reasons. Firstly, because in this period the fascist regime was involved in a serious of imperialist wars, such as the Ethiopian war and the Second World War. Because of that, the regime tried to increase its control over media and art, using them to make propaganda and to manipulate the public opinion in order to mobilize it to war. The second reason concerns the relatively high freedom of speech that the Cinema’s magazine staff achieved in this period, although Vittorio Mussolini, the Duce’s sun, was the magazine director. The magazine had in its staff names such as Gianni Puccini, Giuseppe De Santis, Mario Alicata, Antonio Pietrangeli e Luchino Visconti. After several years criticizing the Italian cinema that was being produced, the group of young filmmakers created Ossessione, like a flag of an idea, as a result of their artistic and antifascist maturity. This dissertation aims to analyze the fascist censorship policies, the propaganda discourses on media, and how the group behind Ossessione used the existing means to create artistic and antifascist resistance, through the denounce of poverty, despair and the lack of options, in a society as such, controlled by an authoritarian fascist regime.